Bilateral agreement for academic years 2010/2011-2013/14 Lifelong Learning Programme (higher education Erasmus) between Universidade Lusíada de Lisboa and Universität Trier - Universidade Lusíada de Lisboa (2015)
- Cooperate in the activities within the EU Lifelong Learning Programme. - Subject area: Law